2022
DOI: 10.23917/jisel.v5i2.18511
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Zakat Literature from 1964 to 2021

Abstract: This research is intended to provide a comprehensive historical and present development of zakat literature through bibliometrics analysis extracted from Scopus database. From 522 articles related to zakat, the findings show that Universiti Utara Malaysia, IMEFM, and Saad, R. A. J have become the most institution, journal and author that published in zakah literature respectively. Moreover, the article from Haniffa, R; Hudaib (2007) is found to be the most cited article worldwide. While Malaysia has become the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Penelitian ini menggunakan pendekatan bibliometrik yang telah diterapkan dalam beberapa penelitian serupa Udomsap & Hallinger, 2020;Supriani, 2022;Alifariki, 2022;Firmansyah & Rahmani, 2022;Fahriza, 2023) ditemukan sekitar 412 artikel yang telah dipilah berdasarkan judul dan abstrak agar sesuai dengan tujuan penelitian sebagaimana telah dilakukan oleh peneliti sebelumnya (Alshater, 2022;Khan, 2020;. Sehingga penelitian ini mengikuti metodologi dari peneliti tersebut untuk melakukan analisis berdasarkan perkembangan artikel tahunan, kutipan, penulis, dan kata kunci.…”
Section: Metodeunclassified
“…Penelitian ini menggunakan pendekatan bibliometrik yang telah diterapkan dalam beberapa penelitian serupa Udomsap & Hallinger, 2020;Supriani, 2022;Alifariki, 2022;Firmansyah & Rahmani, 2022;Fahriza, 2023) ditemukan sekitar 412 artikel yang telah dipilah berdasarkan judul dan abstrak agar sesuai dengan tujuan penelitian sebagaimana telah dilakukan oleh peneliti sebelumnya (Alshater, 2022;Khan, 2020;. Sehingga penelitian ini mengikuti metodologi dari peneliti tersebut untuk melakukan analisis berdasarkan perkembangan artikel tahunan, kutipan, penulis, dan kata kunci.…”
Section: Metodeunclassified
“…Nonetheless, the effectiveness on the taxation policy remains untouched. The bibliometric research on zakat also shows that zakat tax relation is too small to be considered in the overall zakat researches (Supriani et al, 2022). While researchers like Khamis and Yahya (2015) asserts that law enforcement is one of the biggest factors influencing people in paying their zakat obligation, there is still possibility that different policy and taxation system could give different effects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Islamy & Hannase (2021) showed that zakat and waqf promoted national economic growth. The zakat study has also recently experienced considerable development (Supriani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%